2006
DOI: 10.2139/ssrn.918433
|View full text |Cite
|
Sign up to set email alerts
|

Remittances and the Brain Drain

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 22 publications
2
34
0
1
Order By: Relevance
“…In other words we will capture not only the decision of migrants whether to send money home in response to an international difference in cyclical position, but also the decision of workers whether to 24 The other variables in their equation are per capita income in both countries, a measure of the transaction cost, and the exchange rate spread, and a dummy variable for dual exchange rates. Faini (2006) argues that the skill level of the migrant has a negative effect on remittances. 25 The data point representing remittances from Portugal to Moldova looks like an outlier.…”
Section: Resultsmentioning
confidence: 99%
“…In other words we will capture not only the decision of migrants whether to send money home in response to an international difference in cyclical position, but also the decision of workers whether to 24 The other variables in their equation are per capita income in both countries, a measure of the transaction cost, and the exchange rate spread, and a dummy variable for dual exchange rates. Faini (2006) argues that the skill level of the migrant has a negative effect on remittances. 25 The data point representing remittances from Portugal to Moldova looks like an outlier.…”
Section: Resultsmentioning
confidence: 99%
“…2 Some studies find that remittances may decline with increases in income, as Marcelli and Lowell (2005) found for Mexicans in Los Angeles and Du et al (2005) found among remitters to the poor in China. Relatedly, the highly skilled are not necessarily the highest remitters (Faini 2006;. These findings suggest a bell curve relationship between income and remittance volume.…”
Section: Characteristicsinfluencingremittancesmentioning
confidence: 79%
“…DeVoretz and Vadean (2007) show that immigrant households belonging to ethnic groups in which people are more attached to their extended family remit more of their income and over longer periods of their lifetime. Faini (2006) points out that highly skilled migrants remit less than low-skilled because they are more likely to settle permanently and to reunite with their close family in the host country. Lucas (2001), however, argues that highly skilled migrants make a very important contribution to the development of their countries of origin, through remittances, investments and transfer of technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…He found evidence therefore in the case of East Asian migration. On the other hand, Faini (2006) theorises that skilled migrants would remit less than unskilled because skilled migrants are less likely to return in the home country and more likely to reunite with their close family in the host country. This paper does not address the return propensity of skilled migrants.…”
Section: Motivation and Scopementioning
confidence: 99%